Introduction to these Reflections on Maina wa Kinyatti's Kenya: A Prison Notebook. (28th August 2022) - Mathenge, Brian
Abstract : Every society and generations within it are inspired and influenced by similar, yet very distinctive characteristics. They relate within a particular context of struggle. In every generation, there are primary and secondary tasks to be accomplished. Frantz Fanon has consistently reminded us, that: "Each generation must, out of relative obscurity, discover its mission, fulfill it, or betray it" – words that we have held precious within the frameworks of our liberation struggles. They keep reminding us of the revolutionary tasks that history has accorded our generation.